Eating‐disorder psychopathology and driven exercise change models: A latent change score analysis. Issue 12 (3rd November 2020) - Chapa, Danielle A. N.; Kite, Benjamin A.; Forbush, Kelsie T.; Tregarthen, Jenna P.; Argue, Stuart
Abstract: Objective: Approximately 50% of people with eating disorders (EDs) engage in driven exercise to influence their weight or shape and/or to compensate for loss‐of‐control eating. When present, driven exercise is associated with a lower quality‐of‐life, longer hospital stays, and faster rates‐of‐relapse. Despite the seriousness of driven exercise, most treatments for EDs do not target maladaptive exercise behaviors directly. Given the large proportion of patients with an ED who engage in driven exercise and its effect on treatment outcomes, it is critical to understand what predicts change in driven exercise. The purpose of this study was to test whether ED symptoms prospectively predicted change in driven exercise and vice versa. Method: Participants were Recovery Record (RR) users ( N = 4, 568; 86.8% female) seeking treatment for an ED. Participants completed the Eating Pathology Symptoms Inventory (EPSI) monthly for 3 months. Results: In the full sample, dynamic bivariate latent change score analyses indicated that high levels of dietary restraint and restricting prospectively predicted reductions in driven exercise. Among persons with anorexia nervosa (AN), high levels of binge eating predicted increased driven exercise. Among persons with bulimia nervosa (BN), high levels of body dissatisfaction predicted increased driven exercise. Among persons with binge‐eating disorder (BED), high levels of binge eating, purging, and restricting predicted reductions in driven exercise. Discussion: Results highlight changes that may predict increased or decreased driven exercise relative to other ED symptoms for AN, BN, and BED groups. These preliminary findings could inform future research on ED treatment efforts to manage driven exercise.